Blended Learning Program: An Alternative Solution to Improve Students TOEFL Score - Komariah, Endang; Hidayat, Mukhlis; Nurlaili, Nurlaili (AT-TA'LIM, 2019)
This action research aims at finding out how the blended learning can improve students toefl score. The design of this research is an action research which consists of four steps in a cycle, they are: planning, action, analysis and reflection. In planning step the reserachers did FGD which involved the students, instructors, the dean, the head of language centres and staff to discuss the problems and the alternative solution, designed the syllabus and prepared the materials. In the action step, the blended learning was implemented , 50%wasÂ  in Face to Face (F2F) mode and other 50% was in information and technology (IT) mode (CALL, email, WA and SMS).The subjects were 20 students from 16 Study Programs in FKIP at the eight semester who have ever joined TOEFL but have not achieved the target score stated by the university, 477.The implementation of Blended learning was observed and analyzed as the next step. The Reflection result showed that Blended learning could improve the students TOEFL score. The students also enjoyed the activities and they believed blended learning helped them improve their TOEFL score. Therefore it is recommended that the University implement the Blended learning program as an alternative solution to solve the problem.